2020
DOI: 10.1016/j.cois.2020.08.002
|View full text |Cite
|
Sign up to set email alerts
|

How commensal microbes shape the physiology of Drosophila melanogaster

Abstract: The interactions between animals and their commensal microbes profoundly influence the host's physiology. In the last decade, Drosophila melanogaster has been extensively used as a model to study host-commensal microbes interactions. Here, we review the most recent advances in this field. We focus on studies that extend our understanding of the molecular mechanisms underlying the effects of commensal microbes on Drosophila's development and lifespan. We emphasize how commensal microbes influence nutrition and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 65 publications
2
47
0
Order By: Relevance
“…N-acetyl-glutamine), which are directly responsible of host immune regulation and growth. Our results reinforce the notion that the influence of beneficial microbes on Drosophila physiology therefore relies on the intricate network of nutritional, metabolic and immune inputs (86). Further work would be needed to dissect the interdependency of such processes and to reveal the mechanisms underlying the bacterial specificity towards Drosophila immune effectors.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…N-acetyl-glutamine), which are directly responsible of host immune regulation and growth. Our results reinforce the notion that the influence of beneficial microbes on Drosophila physiology therefore relies on the intricate network of nutritional, metabolic and immune inputs (86). Further work would be needed to dissect the interdependency of such processes and to reveal the mechanisms underlying the bacterial specificity towards Drosophila immune effectors.…”
Section: Discussionsupporting
confidence: 87%
“…Specifically, the amidasic activity of PGRP-SCs has been shown to result in dampening the IMD pathway, which appears to be under strong negative regulation in flies (28, 45, 85). This is known as immune tolerance, and it is meant to prevent constitutive activation of the energy-consuming NF-kB pathways (86). In addition, it has been demonstrated that PGRP-SC1 and PGRP-SC2 are required in vivo for full Toll pathway activation by Gram-positive bacteria and for phagocytosis (45, 87).…”
Section: Discussionmentioning
confidence: 99%
“…The interaction with diverse microbiota influences intestinal stem cell function and tissue regeneration [69][70][71]. While we only alluded to this here, a large body of literature focuses on the effects of commensal and pathogenic bacteria on metabolism and immunity of the gut and organism [72,73]. The insight gained on processes controlling adult stem cells using the Drosophila midgut will provide important first principles and testable hypotheses for addition studies in other model organisms and human pluripotent cell culture systems.…”
Section: Conclusion Future Questionsmentioning
confidence: 99%
“…However, the vast majority of symbiotic microorganisms are concentrated in the intestines of insects, where they act as key regulators of the insect host’s multiple lifestyles (including diet and ecological niche; Gupta and Nair, 2020 ). Studies have shown that symbiotic bacteria in the intestinal tract of insects can promote host food consumption and digestion; provide immunity and protection against various predators, pathogens, and parasites; control the success rate of host mating and reproduction; provide essential amino acids, metabolic compounds, and nutrients ( Russell et al, 2014 ; Douglas, 2015 ; Arbuthnott et al, 2016 ; Wielkopolan and Obrępalska-Stęplowska, 2016 ; Engl and Kaltenpoth, 2018 ; Grenier and Leulier, 2020 ; Horak et al, 2020 ). In a recent study, the main roles of insect gut bacteria were demonstrated to be providing essential nutrients, followed by digestion and detoxification ( Jing et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%